Determination of Groundwater Using Geoelectric Methods: Schlumberger Configuration in Rokan Hulu Regency - Febriani, Yeza; Rohman, Riza Ari; Asra, Azmi; Apriniyadi, Mohammad; Wardani, Donata Nariswari Wahyu (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2019)
This study aimed at detecting the presence of groundwater in Masda Makmur Village, Rambah Samo District, Rokan Hulu Regency, using the Schlumberger configuration geoelectric method. The study consisted of 3 sounding points within every 100 m sounding track length. The measurement data is processed using IP2WIN software and Progress to see layer data below the ground level based on the value of the resistivity type. The results showed that the estimated groundwater could be found on track one with a kind of resistivity value of 7,44 Ωm at a depth of 15-22 m. Alleged groundwater can be found on the second track with a type of resistivity value of 75,73 Ωmat a depth of 13-18 m, and the estimated groundwater can be located on the third track with a kind of resistivity value of 82,52 Ωm, 93,26 Ωm. The deeper and the lower resistivity value shows that the layer has the potential as a carrier layer of groundwater (aquifer). Sounding 1 and 2 have the potential to make bore wells which are thought to be depressed aquifer. The results of this study can be used further for mapping the location of community boreholes